Addiction and its brain science - Spanagel, Rainer; Heilig, Markus (Addiction, 2005)
Aims To illustrate how modern neurobiological approaches will help to identify the neurocircuits and genes involved in addictive behavior. Background The current disorder concept of addiction includes neurobiological foundations and neurobiological research assuming irreversible molecular and structural changes within the brain dopamine reinforcement system, constituting the ‘molecular and structural switch’ from controlled drug intake to compulsive drug abuse. However, those irreversible changes have not so far been identified and it is suggested that in addition to the mesolimbic dopamine system, other brain systems including the mesocortical and nigrostriatal pathways as well as their non-dopaminergic feedback-loops might be involved in addictive behavior. Neurobiological approach A three-step neurobiological approach is described that allows in a first step via novel animal models and imaging techniques to identify the neuroanatomical sites mediating voluntary drug intake, reinstatement of drug-seeking behavior, relapse, loss of control and drug intake despite negative consequences. In a subsequent step, forward genetic approaches including quantitative trait loci (QTL)-analysis and gene expression profiling are helpful in identifying so-called candidate genes. In a final step, conditional animal mutants and selective pharmacological tools are used to functionally validate candidate genes. Following this validation process, the transfer to the human situation has to be made and candidate genes have to be verified further in well-phenotyped cohorts of addicted patients. Conclusion This three-step neurobiological approach, that must involve an interdisciplinary team including experimental psychologists, geneticists, molecular biologists and finally clinical addiction researchers, will allow us to understand where and how the addicted brain goes awry.